2017
DOI: 10.18203/2320-1770.ijrcog20170370
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, attitude and practice of family planning methods in a tertiary care hospital, Uttar Pradesh, India

Abstract: Original Research ArticleAwareness, attitude and practice of family planning methods in a tertiary care hospital, Uttar Pradesh, India Uruj Jahan, Kavita Verma*, Shruti Gupta, Renu Gupta, Simmi Mahour, Neha Kirti, Poonam Verma INTRODUCTIONIncreasing population growth is a worldwide problem today and our country with a growth rate of 16 million each year is the second most populous in the world. Copyright: © the author(s), publisher and licensee Medip Academy. This is an open-access article distributed under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 7 publications
2
38
0
1
Order By: Relevance
“…The most common side effects were menstrual irregularities 50 (25%) followed by change in weight 20 (10%) ( Table 5). [14][15][16][17][18] In the present study, 94% of the subjects were aware of one or more methods of contraception which is in consistent with the earlier reports of 95.2%, 97.7% and 100%. [19][20][21] The results also are similar to the international study by Abasiattai 14,22 However, contrast studies in KSA and in Jordan showed a low level of knowledge regarding the contraceptive usage.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The most common side effects were menstrual irregularities 50 (25%) followed by change in weight 20 (10%) ( Table 5). [14][15][16][17][18] In the present study, 94% of the subjects were aware of one or more methods of contraception which is in consistent with the earlier reports of 95.2%, 97.7% and 100%. [19][20][21] The results also are similar to the international study by Abasiattai 14,22 However, contrast studies in KSA and in Jordan showed a low level of knowledge regarding the contraceptive usage.…”
Section: Resultssupporting
confidence: 89%
“…Similar results were found in study conducted at Kanpur, they found 69.6% contraceptive usage in secondary and higher educated women and 62.6% in primary educated women. 15 In other study, Gautam AC et al, found that raise in education status helps in improving acceptance of contraceptive practices. 29 Contraception usage was more in Urban population (71.03%) compared to Rural population.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…10 Prevalence of contraceptive use was 62.9% among the study participants. Majority of them (93.1%) were aware of at least one form of family planning method.…”
Section: Discussionmentioning
confidence: 87%